Information security in e-commerce based on ISO 27001: A systematic review - De La Cruz Rodríguez , Gerson Roberth (2023)
In recent years, with the rapid popularization of eCommerce (electronic commerce), which greatly facilitates the lives of people who, with just one click, have the possibility of acquiring innumerable products regardless of the physical infrastructure of the real world. This growth goes hand in hand with the security of information due to its value, therefore it was necessary to analyze the evidence provided from the investigation to know the current state of information security management in the field of eCommerce. A systematic review has been carried out following the PRISMA guidelines of the published articles found in Scopus, including a total of 6 articles. The results consistently indicate that eCommerce systems are highly vulnerable, and this requires an improvement in information security management and security risk management aware of the threats that are increasing, in order to offer a good cybersecurity service. Currently there are many managers on the market that help to keep company information secure, which cover the needs of the systems and their vulnerabilities as a whole, corresponding to the management of information security related to eCommerce, but the ISO 27001 standard largely covers many areas of information security in a company, which provides greater protection and confidence in customer data.